PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PERCETAKAN RUBY PRINTING - OCTA NILAM LUKKITA; YENI AGUSTINA (SMART Management Journal, 2020)
This study aims to investigate: (1) the effect of reliability on customers’ satisfaction, (2) the effect of responsiveness on customer satisfaction, (3) the effect of assurance on customer satisfaction, (4) the effect of empathy on customer satisfaction, (5) the effect of tangibles on customer satisfaction, and (60 the effects of reliability, responsiveness, assurance, empathy and tangible on customer satisfaction. This was a quantitative study. The research setting was Ruby Printing Bekasi, the research population comprised customers Ruby Printing. The research sample was selected using Lameshaw, resulting in 96,4 rounded to 100. The data collecting technique was a closed questionnaire with answer alternatives using the Likert Scale. The analysis technique was multiple linear regression analysis using F-test and t-test.